Hospital profitability in Indonesia as an emerging market: Internal financial conditions, macroeconomic drivers, and profitability persistence - Rahadian, Dadan; Kusairi, Suhal; Yunita, Irni; Firli, Anisah; Gozali, Alfian Akbar; Prawita, Fat’hah Noor (Edelweiss Applied Science and Technology, 2026)
This study investigates the determinants of hospital profitability in Indonesia as an emerging market by examining internal financial conditions, external macroeconomic and socio-demographic factors, and profitability persistence. Using annual panel data from five publicly listed Indonesian hospitals over 2016–2024, the study applies hospital fixed-effects models and dynamic specifications with lagged return on equity (ROE). Internal financial conditions are represented by composite indices covering liquidity, efficiency, leverage structure, coverage capacity, and profitability margins. The findings show that profitability margins are the strongest and most consistent driver of ROE, while healthier leverage structures also contribute positively to profitability. In contrast, macroeconomic and socio-demographic variables have limited explanatory power once hospital-specific effects are controlled for. Dynamic analysis indicates moderate profitability persistence but does not change the dominant role of internal financial factors. Overall, the study concludes that hospital profitability in emerging markets is shaped mainly by managerial financial decisions rather than external economic conditions, implying that hospital managers should prioritize margin optimization, prudent leverage management, and the use of composite financial indices to monitor financial sustainability.